Corporate Digital Responsibility and Environmental Outcomes in Services: Mediating Effects of ESG Performance and Green Reputation, and the Moderating Influence of Electronic Word of Mouth - Keskin, Halit; Tatoglu, Ekrem; Akgun, Ali E.; Esen, Emel (WILEY, 2026)
This study examines how corporate digital responsibility (CDR) influences environmental outcomes in the service sector, focusing on the roles of environmental, social, and governance (ESG) performance and green reputation as mediating factors. It also tests whether electronic word of mouth (e-WOM) moderates the relationship between ESG performance and environmental outcomes. Data were collected from 233 employees across 65 service firms and analyzed using structural equation modeling and bootstrapping techniques. The findings show that CDR contributes to environmental performance both directly and indirectly through enhanced ESG practices. Green reputation further reinforces the connection between CDR and ESG performance, while e-WOM strengthens the effect of ESG performance on environmental outcomes. Together, these mechanisms illustrate how responsible digital practices, when supported by organizational credibility and employee engagement, can improve sustainability performance. The study offers an integrated framework linking CDR with environmental outcomes and provides practical insights for managers seeking to align digital initiatives with sustainability goals.
Keywords: corporate digital responsibility; electronic word of mouth; environmental outcomes; environmental sustainability; ESG performance; green reputation; services; HUMAN-RESOURCE MANAGEMENT; SOCIAL-RESPONSIBILITY; FINANCIAL PERFORMANCE; IMPACT; MODEL; INNOVATION; DIFFUSION; Business & Economics; Environmental Sciences & Ecology